DOES INSULIN RESISTANCE IMPAIR THE VIROLOGICAL RESPONSE TO PEGINTERFERON/RIBAVIRIN IN CHRONIC HEPATITIS C GENOTYPE 3 PATIENTS? - Laurito, Marcela Pezzoto (2018)
ABSTRACTBACKGROUND:Insulin resistance and diabetes mellitus are common extrahepatic manifestations of chronic hepatitis C (HCV). Insulin resistance assessed by HOMA-IR is associated with low rates of sustained virological response, especially in HCV genotype 1 positive patients treated with peginterferon/ribavirin. The effect of insulin resistance on sustained virologic response in HCV genotype 3 positive patients who were treated with peginterferon/ribavirin still remains unclear.OBJECTIVE:To evaluate the impact of insulin resistance on sustained virological response in HCV genotype 3 patients treated with peginterferon/ribavirin.METHODS:A retrospective multicenter study was performed to evaluate the impact of insulin resistance on sustained virological response in non-diabetic HCV genotype 3 positive patients treated with peginterferon and ribavirin. A total of 200 HCV genotype 3 positive patients were enrolled in the study. All patients were non-diabetic. Each patient had a HOMA-IR value measured before the initiation of HCV treatment with peginterferon/ribavirin. The treatment duration was at least 24 weeks. The HOMA-IR cut-off was defined in the study as ≥2.5 due to the coefficient of correlation with sustained virological response of 0.202 (P=0.004).RESULTS:Univariate analysis showed that age, aspartate aminotransferase, platelets, stage of fibrosis and HOMA-IR were predictors of sustained virological response. However multivariate analysis showed advanced fibrosis [OR=2.01 (95%CI: 0.986-4.119) P=0.05] and age [OR=1.06 (95%CI: 1.022-1.110) P=0.002] as negative predictors of sustained virological response.CONCLUSION:In this retrospective multicenter study of non-diabetic HCV genotype 3 positive patients, insulin resistance was not associated with the sustained virological response in patients who were treated with peginterferon/ribavirin.